DESIGN OF LABORATORY ASSIGNMENTS AIMED AT THE FORMATION OF EXPERIMENTAL SKILLS - Khabib Shukurullayevich Abdullayev (Galaxy International Interdisciplinary Research Journal, 2022)
The article covers the development, theoretical justification and application in the educational process of the methodology for the formation of experimental skills of future teachers in general physics laboratories.